Propositional-frame organization of word-formation type “proper name + suffix -ец-” (on the example of the neologisms functioning in mass media of Kyrgyzstan) (Eurasian Journal of Philology Science and Education, 2015)
In the article there are considered the stories of propositional and frame formation analyses. There are substantiated the application possibility of the method of propositional and frame modeling for the description of complex units of word formation and neologisms. The results of the propositional-frame description of word-formation type are presented inthe article “Proper name + suffix -ец” on the example of the neologisms functioning in mass media of Kyrgyzstan. Description of the new words specifics in the mainstream of cognitive derivatology allows to draw conclusions not only on the same neologism’s system organization within the same type of word-formation, but also to describe the mental structures underlying them. The article examines some of the cultural concepts in order to confirm the occurrence of conditioning and shape features of the new words by the national mentality. This research reveals the kind of question about the specifics of the Russian language in Kyrgyzstan. An analysis of neologisms in the cognitive aspect is madeconclusions, the worldview of the Russian-speaking Kyrgyz citizen changes in a result of living in the conceptual systems of the two languages – Russian and Kyrgyz.
Keywords: proposition; frame; word-formation type; neologism.